The The Influence of Gross Regional Domestic Product (GRDP), Local Own-Source Revenue (PAD), and Balance Funds on Capital Expenditure Allocation in All Provincial Governments in Indonesia in 2019-2021 - Simanjuntak, Daniel Parulian (Jurnal Pajak dan Keuangan Negara (PKN), 2024)
This research aims to determine the influence of gross regional domestic product (GRDP), local own-source revenue (PAD), and balance funds on local government capital expenditure allocation, both partially and simultaneously. The population in this study consists of all provincial governments in Indonesia, totaling 34 provincial governments from 2019 to 2021, resulting in a total sample size of 102 observations. This research uses Budget Realization Report (LRA) data for capital expenditure, PAD, and balance funds data, while GRDP data is obtained from BPS-Statistics Indonesia. The multiple linear regression technique is used for longitudinal/panel data in hypothesis testing. The results of the study indicate that GRDP does not significantly influence capital expenditure allocation; otherwise, PAD and balance funds have a significant positive impact on capital expenditure allocation. This research contributes to the literature on state and regional financial management in the context of state and regional revenue and expenditure.